Factors influencing consumer acceptance of online banking: a case study on Kuala Lumpur area / Nuramira Azrai and Anis Nabilah Abdul Hamid - Azrai, Nuramira; Abdul Hamid, Anis Nabilah (Faculty of Business and Management, 2014)
Internet banking has becoming the most advance channel in financial service and offers many benefits to financial institutions and as well to the consumer. Internet banking provide a lot of advantages such as quick service delivery, reduced frequency of going to banks physically and reduced cash handling. The purpose of this study is to investigate the factors that influence the acceptance of Internet banking in Kuala Lumpur area. There are three factors that influencing the Internet banking acceptance which were ease of use, security and privacy, quality of internet connection. The study follows descriptive research using survey methods. A set of questionnaires of multiple choice and five (5) point likert scale was developed and 100 questionnaires were distributed around Kuala Lumpur area. Frequency analysis, reliability test, correlation analysis, regression analysis, Durbin Watson and coefficient of determination have been chosen as the method to find the result. The findings indicated that ease of use is the most factors that influence the acceptance of Internet Banking in Kuala Lumpur area compared to security and the quality of internet connection. As for future researcher, it recommended that this study can be conduct at different state in Malaysia such as in rural area to know more about the factors that can influence the acceptance of online banking usage.